An attitude control system for cubesat satellites using an adaptive L1 norm control method (2019)
This research explored an alternative solution to the problem of satellite attitude control using a control method that makes robust the control maneuvers and that can handle system dynamics uncertainties. The novel L1 norm adaptive control method was chosen, and respective techniques were explored implemented and modified to solve the satellite attitude control problem SACP